Tobacco and myocardial infarction: is snuff less dangerous than cigarettes?. Issue 6864 (21st November 1992) - Huhtasaari, F.; Asplund, K.; Lundberg, V.; Stegmayr, B.; Wester, P. O.
Abstract : OBJECTIVE--To estimate the risk of myocardial infarction in snuff users, cigarette smokers, and non-tobacco users in northern Sweden, where using snuff is traditional. DESIGN--Case-control study. SETTING--Northern Sweden. SUBJECTS--All 35-64 year old men who had had a first myocardial infarction and a population based sample of 35-64 year old men who had not had an infarction in the same geographical area. MAIN OUTCOME MEASURE--Tobacco consumption (regular snuff dipping, regular cigarette smoking, non-tobacco use) and risk of acute myocardial infarction. RESULTS--59 of 585 (10%) patients who had a first myocardial infarction and 87 of 589 (15%) randomly selected men without myocardial infarction were non-smokers who used snuff daily. The age adjusted odds ratio for myocardial infarction was 0.89 (95% confidence interval 0.62 to 1.29) for exposure to snuff and 1.87 (1.40 to 2.48) for cigarette smoking compared with non-tobacco users, showing an increased risk in smokers but not in snuff dippers. Regular cigarette smokers had a significantly higher risk of myocardial infarction than regular snuff dippers (age adjusted odds ratio 2.09; 1.39 to 3.15). Smoking, but not snuff dipping, predicted myocardial infarction in a multiple logistic regression model that included age and level of education. CONCLUSIONS--In middle aged men snuff dipping is associated with a lower risk of myocardial infarction than cigarette smoking.